PENGARUH KECERDASAN EMOSIONAL TERHADAP MOTIVASI BELAJAR MATEMATIKA SISWA KELAS IV SEKOLAH DASAR ISLAM BABUSSALAM DURENAN KABUPATEN TRENGGALEK TAHUN AJARAN 2017/2018 - Muhammad Farhan Faizi (Program Studi Pendidikan Guru Sekolah Dasar FKIP Universitas Pasundan, 2018)
Mathematics is one of compulsory science for all human beings. However, this science is often a scourge for students so that the motivation of students to this science is low. Emotional intelligence is one of the factors that influence the high intrinsic motivation that the learners have. From the exposure, the researchers took the formulation of the problem